2007
DOI: 10.1071/en07012
|View full text |Cite
|
Sign up to set email alerts
|

Iron-binding ligands and their role in the ocean biogeochemistry of iron

Abstract: Environmental context. It is now well accepted that iron is an essential micronutrient for phytoplankton growth in many areas of the global ocean, even though this element is present in seawater in extremely low abundance. It is also known that most of the iron in seawater is present as complexes formed with ligands of natural organic matter whose nature and origin remain largely unknown. Here we consider how these iron-complexing ligands might have evolved during geological time, what factors may have given r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
160
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 155 publications
(167 citation statements)
references
References 123 publications
(148 reference statements)
7
160
0
Order By: Relevance
“…Fe-binding organic ligands are critical for Fe biogeochemistry, improving its solubility and affecting its reactivity to support phytoplankton growth Hassler et al, 2011aHassler et al, , 2012. The distribution of Fe-binding organic ligands in the open ocean is compatible with multiple biological sources associated with Fe-stress and its recycling/remineralisation (Hunter and Boyd, 2007). However, despite their recognised importance, the production pathways, nature and binding mechanisms of insitu Fe-binding ligands are mostly unknown (Gledhill and Buck, 2012).…”
Section: Iron (Fe) Limitationmentioning
confidence: 99%
“…Fe-binding organic ligands are critical for Fe biogeochemistry, improving its solubility and affecting its reactivity to support phytoplankton growth Hassler et al, 2011aHassler et al, , 2012. The distribution of Fe-binding organic ligands in the open ocean is compatible with multiple biological sources associated with Fe-stress and its recycling/remineralisation (Hunter and Boyd, 2007). However, despite their recognised importance, the production pathways, nature and binding mechanisms of insitu Fe-binding ligands are mostly unknown (Gledhill and Buck, 2012).…”
Section: Iron (Fe) Limitationmentioning
confidence: 99%
“…This indicated that the ligands presumably coming from the phytoplankton are relatively weak, supporting the conclusion of Rijkenberg et al (2008b) that phytoplankton can modify ligand characteristics. Others stated that ligands related to phytoplankton activity belong to the relatively strong ligand group (Rue and Bruland, 1997;Cullen et al, 2006;Hunter and Boyd, 2007).…”
Section: Fe-binding Ligandsmentioning
confidence: 99%
“…However, a photoactive siderophore that belongs to the L2 class has now been reported (3). Moreover, uncertainties remain about the nature of organic ligands that bind iron (12,16). Ligands too weak to fall within the analytical window of the competitive ligand exchange technique are also not detected (17); thus, their importance for iron biogeochemistry is likely to be underestimated.…”
mentioning
confidence: 99%
“…Both experimental (4,14) and modeling (15) observations agree that organic complexation is necessary to maintain iron solubility and bioavailability in the ocean. In oceanic waters, two classes of organic ligands (L1 and L2) have been identified on the basis of their binding affinities for iron (12). It is widely accepted, from comparable conditional stability constants, that siderophores produced by bacterioplankton (i.e., heterotrophic and autotrophic bacteria) belong to the strongest class (L1) of organic ligands.…”
mentioning
confidence: 99%
See 1 more Smart Citation